2012
DOI: 10.1007/s10495-012-0705-6
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide nanoparticles induce oxidative DNA damage and ROS-triggered mitochondria mediated apoptosis in human liver cells (HepG2)

Abstract: The wide scale use of Zinc oxide (ZnO) nanoparticles in the world consumer market makes human beings more prone to the exposure to ZnO nanoparticles and its adverse effects. The liver, which is the primary organ of metabolism, might act as a major target organ for ZnO nanoparticles after they gain entry into the body through any of the possible routes. Therefore, the aim of the present study was to assess the apoptotic and genotoxic potential of ZnO nanoparticles in human liver cells (HepG2) and the underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
402
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 677 publications
(453 citation statements)
references
References 56 publications
27
402
2
2
Order By: Relevance
“…Thus, the results of the present study indicate that 23,24-dihydrocucurbitacin B may induce apoptosis by increasing intracellular ROS and decreasing the ΔΨm. Several anticancer drugs act against cancer by producing ROS (21,22); for example, afferent A disrupts the ΔΨm and induces oxidative stress, ultimately inducing apoptosis in osteosarcoma cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the results of the present study indicate that 23,24-dihydrocucurbitacin B may induce apoptosis by increasing intracellular ROS and decreasing the ΔΨm. Several anticancer drugs act against cancer by producing ROS (21,22); for example, afferent A disrupts the ΔΨm and induces oxidative stress, ultimately inducing apoptosis in osteosarcoma cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the Johnsen's scoring relate to germ cells degenerations. reported that ZNP exposure in HepG2 cells increases apoptotic cell death [36]. Recently, some NPs types have been identified as a novel class of autophagy activators and inducers of autophagic cell death [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…This probe has been utilized successfully in previous investigations of ROS generation after exposure of different cells in vitro and ex vivo to a wide range of nano-sized materials (i.e. 9,32,35,37,46,[51][52][53]. Finally, it is important to further state that the flow cytometric evaluation of ROS is an established method and previously used in cell lines to detect NM-induced damage [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…This property is believed to be size-dependent and only occurs at around 10-20 nm [7]. Iron oxide is one of the few NMs with current clinical applications and approved by the US Food and Drug Administration since 1996 [8,9].Carbon NM constructs and in particular carbon nanotubes are utilized in a diverse range of applications relevant to nanomedicine. These include implementation in drug or gene delivery systems [10][11][12][13], as targeting and photosensitizing agents [14], as tissue scaffolding [15], utilization in the treatment of arthritis [13] or to aid in imaging techniques [16][17][18].…”
mentioning
confidence: 99%